2020
DOI: 10.1111/tbj.13827
|View full text |Cite
|
Sign up to set email alerts
|

The actual benefit of intraoperative radiation therapy using 50 kV x‐rays in early breast cancer: A retrospective study of 676 patients

Abstract: This French study reports the 5-year results of partial-breast irradiation using intraoperative radiation therapy (IORT) with 50 kV x-rays, in select early breast cancer patients. We report a retrospective analysis of 676 consecutive early breast cancer patients treated between November 2011 and December 2015 by partial-breast irradiation using the INTRABEAM ® system. Patients were highly selected based on the ASTRO and GEC-ESTRO criteria and underwent breast-conservative surgery and IORT, completed with addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
(31 reference statements)
0
9
0
1
Order By: Relevance
“…However, with longer follow-up, a recent 2021 update of TARGIT-R reported a 5-year IBTR rate of 6.6% [ 20 ]. A summary of photon IORT trials is shown in Supplementary File — Table S2 [ 18 , 20 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, with longer follow-up, a recent 2021 update of TARGIT-R reported a 5-year IBTR rate of 6.6% [ 20 ]. A summary of photon IORT trials is shown in Supplementary File — Table S2 [ 18 , 20 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, the rate of tumor proliferation is reduced and local tumor control is achieved (28). Even though IORT has always been taken advantage of in the treatment of early-stage breast cancer, it is recently used in boost therapy for whole breast irradiation in high risk breast cancer patients with a favorable breast cancer prognosis (29).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple prospective non-randomised studies have published their results of using TARGIT-IORT, with similar outcomes in over 3000 patients treated with TARGIT-IORT from France, Germany, Denmark, Switzerland, and others [16][17][18][19][20][21] . By 2019, over 260 centres in 38 countries worldwide had treated over 45,000 breast cancer patients with TARGIT-IORT (https://targit.org.uk) 22 .…”
mentioning
confidence: 98%